2022
DOI: 10.3389/fvets.2022.822432
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic/Pharmacodynamic Relationships of Tulathromycin Against Actinobacillus pleuropneumoniae in a Porcine Tissue Cage Infection Model

Abstract: Tulathromycin is a semi-synthetic macrolide antibiotic that is highly effective in treating respiratory tract bacterial infections. We evaluated the in vivo antibacterial activity of tulathromycin against Actinobacillus pleuropneumoniae in piglets and determined its pharmacokinetic/pharmacodynamic (PK/PD) relationships using a tissue cage infection model. A. pleuropneumoniae (108 CFU/ml) was exposed to tulathromycin via intramuscular injection followed by a collection of cage tissue fluids at various intervals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…The C max values of reference drug (Draxxin) and four generic drugs (Tulaject, Tulazen, Tulshot and T-raxxin) were 1100.08 ± 102.97, 1027.97 ± 77.06, 1110.04 ± 56.78, 1031.15 ± 80.09 and 1028.99 ± 18.95 ng/mL, respectively. The MICs of tulathromycin were 0.25 µg/mL and 0.03 µg/mL against A. pleuropneumoniae and P. multocida in the infection model [20,21]. The C max values of tulathromycin from the reference and generic products were at least four times the MIC (≤0.25 µg/mL) against common microorganisms such as A. pleuropneumoniae and P. multocida.…”
Section: Discussionmentioning
confidence: 96%
“…The C max values of reference drug (Draxxin) and four generic drugs (Tulaject, Tulazen, Tulshot and T-raxxin) were 1100.08 ± 102.97, 1027.97 ± 77.06, 1110.04 ± 56.78, 1031.15 ± 80.09 and 1028.99 ± 18.95 ng/mL, respectively. The MICs of tulathromycin were 0.25 µg/mL and 0.03 µg/mL against A. pleuropneumoniae and P. multocida in the infection model [20,21]. The C max values of tulathromycin from the reference and generic products were at least four times the MIC (≤0.25 µg/mL) against common microorganisms such as A. pleuropneumoniae and P. multocida.…”
Section: Discussionmentioning
confidence: 96%
“…They showed that the AUC 168 h /MIC required to achieve a reduction of 1, 2, 3, and 4 Log 10 CFU/mL of H. parasuis was 366.06, 552.51, 728.47, and 916.90 h in serum, and 507.20, 1,227.11, 2,126.44, and 3,462.62 h in lung tissue, respectively. Yao et al ( 17 ) studied the PK/PD of tulathromycin against APP in a tissue-cage infection model. They discovered that %T > MIC was the best PK/PD parameter for predicting the antibacterial effect ( R 2 = 0.9421) and the values required to achieve a reduction of 1 Log 10 CFU/mL and 3 Log 10 CFU/mL were 50.8 and 96.38%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For measurement of the drug concentration, equal volumes of sample and acetonitrile were mixed and centrifuged (12,000 × g , 10 min, 4°C). Then, the supernatant (200 μL) was added to the mobile phase (800 μL), vortex-mixed, and passed through a 0.22-μm filter membrane for analysis by HPLC-MS/MS according to a protocol described previously ( 17 ). The limit of detection and limit of quantification were 5 and 10 ng/mL, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are more than 19 serovars of A. pleuropneumoniae; therefore, the protective effect of the currently available vaccine is not satisfactory [8]. Consequently, antimicrobials still play an important role in the prevention and treatment of this disease, including cephalosporins, fluoroquinolones, and macrolides [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%